Penerapan E-Assigment Sebagai Upaya Guru Dalam Memberikan Penilaian Hasil Belajar Berbasis Digital - Chairu Nisaa’ Nasution, Ramadani Hasibuan, Salwa Sabrina, Julianti Sembiring, Laras Hilda Samura, No (Journal of Educational Research and Humaniora (JERH), 2023)
The purpose of this research discipline is to find out how students respond to using the e-assignment that the author designed, where the principle of e-assignment itself is an innovation to facilitate and simplify assignments given to students, so that they can be well received and understood by students. The author uses a qualitative descriptive research method. A qualitative descriptive research method is a type, design, or research design that is commonly used to examine natural research objects or in real conditions and not set up as in experiments. Descriptive itself means that the results of the research will be described as clearly as possible based on the research that has been done without drawing any conclusions based on the results of the research. The results of the study show that students are very happy in doing assignments or exam questions carried out through this e-assignment, because they get new experiences that they may not have gotten from their teachers, so that the scores obtained by these students get maximum results. If later other teachers can apply the e-assignment application this could have a good impact, because after the teacher applies digital media as a means of teaching and learning process it makes students tend to be active and focus on participating in Civics learning activities so that student learning outcomes in Civics subjects increase.